PARASITES AND PREDATORS OF THE MAIN PEST OF STONE-FRUIT CROPS IN THE SHEKI-ZAKATALY ZONE OF AZERBAIJAN - Z. M. Mamedov; E. M. Muradova (Юг России: экология, развитие)
Researches made by us have shown that 31 species of vermin and 13 species of predators play significant role in regulation of the quantity of 11 most harmful insects which inhabit in fruit tree gardens of Sheki-Zakatala region of Azerbaijan. In general 44 species of entomophages which are related to the order of hymenopterans, neuropteras, coleopteras and dipteras. Their host significance in regulation of the quantity of hosts was identified.